Unveiling the Role of ESG in Ensuring Low-Carbon Energy Transition - Makhmudov, Samariddin; Madaminov, Sardorbek; Kurbanov, Daniyor; Nabiyeva, Nilufar; Sabirov, Khamid; Rajabov, Nazirjon; Ruzmetova, Maxbuba (International Journal of Energy Economics and Policy, 2025)
Currently, the position of ESG in energy transition is becoming one of the hot research topics in the academia. In this context, this work studies the impact of ESG on low-carbon energy risk in the panel of 148 nations over the period 2000-2023. As an econometric tool, Method of Moments Quantile Regression is employed which is robust method for heteroscedasticity. The estimations reveal that the promotion of ESG reduces low-carbon energy risk across all the quantiles from 10% to 90%. Furthermore, sub-dimension tests are conducted using environmental, social and governance indices of ESG separately. They also show the negative impact on low-carbon energy risk. Overall, the findings are aligned with both theoretical and economic linkages.